University teachers’ attitude and ability towards the practice of using computer technology in classrooms with special focus on Pakistan - Ghulam Rasool, Memon, Dr. (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.